THE ROLE OF MAGNETOTACTIC BACTERIA IN FORMATION OF NATURAL MAGNETISM OF UKRAINE SOILS - Menshov, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The study of the role of magnetotactic bacteria in the formation of soil magnetism is important for the investigation of natural unpolluted soils. We consider the genesis of the magnetic properties of the soil, the development of carriers of magnetism under the soil formation, the use of magnetic methods for determining the soil state, erosion, the effects of fires, degradation, destruction, water regimes, compaction, productivity, fertility, humus content, physicochemical parameters that are used in agronomy and soil science. Magnetotactic bacteria are found in soils rich in iron. Magnetosomes of pure stable single-domain grains (SD) are formed intracellular and identified in magnetic soil extracts by transmission electron microscopy. Natural soils can contain both stable single-domain grains – magnetosomes of bacterial origin, and superparamagnetic grains (SP) of inorganic origin. Magnetotactic bacteria form the magnetic properties of natural soil in case of non-availability of the lithogenic base influence, hydrocarbons and man-made pollution impact. This article studies the distributions of the magnetic susceptibility in the genetic horizons of soils of Ukraine of different origin. The magnetic mineralogical parameters are analyzed too. The natural soils with the predominance of pedogenic magnetic signal and the organic formation of magnetic minerals under the influence of magnetotactic bacteria of the Kharkov Oblast have been studied. Moreover, the natural soils with both lithogenic and pedogenic signal of the Carpathians were investigated. The soils affected by hydrocarbons of the Precarpathians of Ukraine were considered. Man-made pollution of the urban soils of Dnipro agglomeration was analyzed. To increase the quality of the interpretation of soil magnetism to study magnetotactic bacteria we recommend using the electron microscopic high-precision images (SEM, TEM) and agrochemical parameters.